IMPLEMENTATION OF ISO 9001 REQUIREMENTS AND THE ECONOMIC EFFICIENCY OF SMALL AND MEDIUM-SIZED ORGANIZATIONS - Dominik ZIMON (Modern Management Review, 2013)
Implementation of ISO 9001, especially for small and medium size organizations is undoubtedly a significant investment. It is, therefore, an important question of its viability. Available literature data suggest a lack of conclusive arguments concerning the implementation of a positive ratio requirements of ISO 9001 to increase the financial efficiency of the organization. So puzzling is the significant popularity of the implementation of system solutions. The article elaborates on the impact of the implementation of ISO 9001 on the economic efficiency of the organization. The overall aim of the research carried out in 2010 was to determine the effects of the implementation of the quality management system according to ISO 9001 on the economic efficiency of small and medium-sized organizations. For this purpose, the analysis of financial statements, and then the compilation of the results of the two groups of organizations were made: the organization with implemented quality management system according to ISO 9001, organizations which decided not to implement of ISO 9001. An important factor in selecting the research group was that the organizations surveyed operate in conditions as close as possible outside and represented one industry. The selection for the organization of such a group would minimize the effect of different external factors on their economic efficiency. As a result of the search 22 companies were selected in the framework of a purchasing group (implementing a common strategy, logistics, marketing and offering a similar range of products).